PENGARUH LIKUIDITAS, REPUTASI KAP, OPINI AUDIT TAHUN SEBELUMNYA DAN UKURAN PERUSAHAAN TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2016-2018 - I Gusti Ayu Intan Iswari; Made Yudi Darmita (Journal Research of Accounting, 2020)
The going concern audit opinion is an audit opinion that issued by an auditor to ascertain the continuity of the companies. The continuity of the companies affected by internal’s problems in the company itself like financial condition, human resource, company culture, the knowledge of technology, internal’s supervision, and it could be some problem outside the company like market, monetary conditions, social, political, etc. Some research showed that many factor which encourage an auditor to publish going concern audit opinion are different and the result is not conclusive. Therefore, this research aims to re-examine the factors that affected going concern audit opinion. The factors which examine in this research are liquidity, the reputation of public accountant firm, last year audit opinion, and firm size. This research used manufacturing companies in Indonesian Stock Exchange year 2016-2018 as sample. As the result of purposive sampling, obtained a total of 48 manufacturing companies that fit with the sample criterias. The examine of hypotheses in this research used logistic regression analysis. The result of this research showed that going concern audit opinion affected by liquidity and last year audit opinion, and not affected by the reputation of public accountant firm and firm size.